Desinformação científica no Twitter : fixação de crenças em torno da cloroquina durante a pandemia da covid-19 - Fabio Amaral de Oliveira Paes (2022)
The spread of disinformation related to the interpretation of information of a scientific nature illustrates the informational scenario experienced in the context of the covid-19 pandemic, especially on online social media platforms. At the center of the debate, the scientific controversy surrounding chloroquine as a supposed cure for covid-19 highlighted tensions in which the scientific discourse itself was being appropriated for the propagation of information that went against the advancement of the knowledge produced by science. In view of this finding, this research investigates the phenomenon of scientific disinformation on Twitter, a very popular platform in the debate of topics that impact society, seeking to understand to what extent the dispute of meanings around Chloroquine reveals specificities of the contemporary context of scientific disinformation. The methodological procedures adopted were divided into four stages. In the first, through exploratory research, we seek to contextualize the disputes of meanings about Chloroquine through the elaboration of a timeline created with the TimelineJS tool. To this end, we manually collected different sources of information, such as news hyperlinks, posts on social media platforms, opinions and technical notes that were related to the context of the dispute over chloroquine. In the second stage, observing the topics that dominated the conversation on the Twitter platform, through tools such as Trendinalia and Trendin, we searched for hashtags and keywords that demarcated debates about Chloroquine on the platform. Then, we collected data on Twitter with the help of the Scweet project. In the third step, we configured the corpus having as an analytical operator the number of times a particular post was shared. Also at this stage, we identified the main themes and users arising in the context of scientific disinformation about chloroquine. In the fourth methodological step, we analyzed the research corpus, composed of 50 tweets, based on the dogmatic methods of establishing beliefs proposed by Charles Sanders Peirce (1839-1914), namely: tenacity, authority and a priori. As a result, we conclude that the methods of fixing beliefs help us on social understanding of disinformation, beyond the scope of intentionality, through belief systems that evoke layers of different meanings. The fixation of belief by tenacity was observed as slightly predominant, which refers to the adoption of beliefs previously taken as true, followed by the method based on the judgment of reason itself, based on logical arguments for the validation of beliefs. Finally, it was also relevant for the construction of discourses, among which the defense of non-scientifically validated medicines, the method of authority, in which we highlight authority figures with power of influence, with special prominence of political, medical and science in opinion formation.